Optimization of process parameters in bioreduction of silver nanoparticles by pycnoporus sanguineus - Chan, Stephanie; Mat Don, M. (2013)
Controlling the size of nanomaterials are attracting great interest in the research on scientific and technological applications because of their unit properties for achieving specific processes especially in biological and medical applications. Microbial assisted biosynthesis of nanoparticles is of growing potential in the area of bionanotechnology compared to chemical synthesis when dealing with medical and pharmaceutical applications. A simple and effective approach for AgNPs synthesis by Pycnoporus sanguineus was demonstrated and the effect of production mode on controlling size of AgNPs produced was studied. Culture supernatant of Pycnoporus sanguineus was used to synthesis AgNPs of nanosize. One factor at a time (OFAT) method was employed to perform optimization on process parameter such as inoculum size and AgNO 3 concentration. The morphology, uniformity and concentration of AgNPs were investigated using dynamic light scattering (DLS) zetasizer and atomic absorption spectroscopy. It was observed that increase in inoculum size leads to decrease in size of AgNPs and increase of AgNPs concentration. Hence, it can be deduced that optimizing the bioprocess parameters led to superior control of AgNPs size. © (2013) Trans Tech Publications, Switzerland.